A carbon dot-based hybrid fluorescent sensor for detecting free chlorine in water medium. Issue 5 (14th January 2016) - Ding, Yanjun; Ling, Jiang; Cai, Jifeng; Wang, Suiping; Li, Xingmei; Yang, Minghui; Zha, Lagabaiyla; Yan, Jie
Abstract : There are two fluorescence peaks for the CD–RhB nanohybrid and the fluorescence of CDs would be quenched with the addition of NaClO while the peak of RhB almost remains constant and an obvious color change (rose red to lilac) accompanies the process which is very convenient to distinguish by the naked eye. Abstract : A novel fluorescent sensor has been prepared for the quantitative detection of free chlorine in water medium. The sensor contains a fluorescent carbon dot (CD)–rhodamine B (RhB) nanohybrid, which exhibits their respective emission peaks at 445 and 580 nm under an excitation wavelength of 380 nm. The fluorescence of CDs could be quenched by free chlorine through the combination of chemical bonds and energy transfer while the peak of RhB almost remains constant, leading to color changes that can be recognized by the naked eye. The designed sensor could achieve the detection of free chlorine rapidly with a detection limit as low as 4 μM.